1978
DOI: 10.1111/j.1464-410x.1978.tb02816.x
|View full text |Cite
|
Sign up to set email alerts
|

The Site of Recurrence of Non‐Infiltrating Bladder Tumours

Abstract: A study of 56 cases of non-infiltrating bladder tumour showed a striking difference in the distribution within the bladder of the primary and the recurrent tumours. More than three-quarters of the primary tumours were confined to a restricted area near a ureteric orifice whereas only one-fifth of recurrent tumours were found in this site. By far the commonest site for recurrent tumours was the postero-superior wall of the bladder. Forty-five recurrent tumours formed in the air bubble region, a site in which no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0
1

Year Published

1980
1980
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(45 citation statements)
references
References 5 publications
4
39
0
1
Order By: Relevance
“…That partial injury only to the most super®cial layer allows the implantation of tumour cells is important, because this phenomenon is in accordance with the clinical observation [4] that faint injuries made by endoscopic abrasion are associated with frequent tumour recurrence. In addition, the cross-sectional appearance of a minute tumour growing only at the site of the injured mucosa surrounded by normal epithelium suggests that implantation of the tumour has only just begun.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…That partial injury only to the most super®cial layer allows the implantation of tumour cells is important, because this phenomenon is in accordance with the clinical observation [4] that faint injuries made by endoscopic abrasion are associated with frequent tumour recurrence. In addition, the cross-sectional appearance of a minute tumour growing only at the site of the injured mucosa surrounded by normal epithelium suggests that implantation of the tumour has only just begun.…”
Section: Discussionsupporting
confidence: 73%
“…They speculated that this could be caused by cell fragments which separated from the tumour and¯oated to the vault, assisted by adherent gas bubbles, during TURBT. Page et al [4] presented a similar report and suggested that there were many recurrences at the posterosuperior wall of the bladder, perhaps because this part was easily injured at the time of endoscopic surgery.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In addition, urothelial carcinoma cells in animal models have been shown to be capable of adhering to urothelium and subsequently growing into tumors, especially when the urothelium has been previously injured (48 -50). Tumor cells may be implanted in other urothelial sites secondary to cystoscopic manipulation (51,52). The fieldcancerization theory, which has been shown to be important in the development of multicentric squamous cell carcinomas of the head and neck (53 -55), suggests that multifocal urothelial carcinomas arise secondary to numerous independent mutational events at different sites within the urothelial tract as a consequence of external cancer-causing influences.…”
Section: Discussionmentioning
confidence: 99%
“…85% of patients will relapse, mainly during the first postoperative year (Heney et al, 1982;Dalesio et al, 1983;Torti et al, 1987;Gkritsios et al, 2013). Many recurrences are probably new tumors derived from urothelial dysplastic areas, but a significant proportion can be derived from tumour cells released during resection and eventually implanted in the injured areas (McDonald et al, 1956;Weldon et al, 1975;Page et al, 1978;Soloway et al, 1980;Hyacinthe et al, 1995;Selman et al, 2011).…”
Section: Introductionmentioning
confidence: 99%